Penerapan Sanksi Etika Profesi Terhadap Anggota Polisi Yang Melakukan Pemerasan - Karina Hasiyanni Manurung; Kayus Kayowuan Lewoleba (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Professional ethics are indispensable in law enforcement, especially for police institutions like Indonesia. Police officers who abuse their authority such as being involved in acts of extortion will get legal consequences and also ethical sanctions along with administrative sanctions. Several factors also cause the police to commit extortion.  The handling of sanctions against police who commit extortion is regulated in the Criminal Code and in addition to getting ethical sanctions, members of the National Police who violate the Police Professional Code of Ethics will also be subject to administrative sanctions as stipulated in the Regulation of the National Police of the Republic of Indonesia Number 7 of 2022 concerning the Professional Code of Ethics and the Code of Ethics Commission of the National Police of the Republic of Indonesia. This research uses the normative juridical method with a statute approach and conceptual approach. Therefore, it is necessary to increase public awareness, training, and clear law enforcement to reduce police officers who commit extortion and to maintain the professionalism of the police force.